(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background: To alleviate pain associated with rheumatic diseases, musculoskeletal or osteoarticular disorders, and other similar conditions, many people turn to non-steroidal anti-inflammatory medicines (NSAIDs). Chronic therapy is a major cause of morbidity and mortality, even though NSAIDs are usually well tolerated. In reality, patients on NSAIDs have a substantially greater risk of gastrointestinal events (complications). Researchers in pharmacology are looking into COX-2 inhibitors, a type of NSAID that shows promise in improving gastrointestinal tolerance. This is because the demand for nonsteroidal anti-inflammatory drugs (NSAIDs) is growing. The purpose of this research was to determine the frequency of gastrointestinal (GI) events in patients who took non-selective or selective non-steroidal anti-inflammatory drugs (NSAIDs) for three months or longer, either on their own or in conjunction with other antiplatelet medications (such as aspirin or clopidogrel). Methods and patients: 362 people who have experienced persistent gastrointestinal distress for at least three months were part of the cross-sectional and comparative investigation. Patients were retrieved from various healthcare facilities, including emergency rooms, rheumatology clinics, general inpatient wards, and medical counseling clinics. We followed the OGD protocol as the method for diagnosis.